Hydrogel system based on oxidized gastrodia elata stem polysaccharide as well as preparation method and application of hydrogel system

By oxidizing Gastrodia elata stem polysaccharides and grafting chitosan to form a Schiff base cross-linking network, the problems of high replacement frequency and limited recovery effect of hydrogel dressings were solved, resulting in a stable wound dressing that improves wound recovery effect and service life.

CN121445941APending Publication Date: 2026-02-03NANJIANG COUNTY PEOPLES HOSPITAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511602163.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-04
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing hydrogel dressings require frequent replacement, have limited recovery effects, and the nanomedicine carriers are easily decomposed, making it difficult to effectively act on the wound surface for a long time.

Method used

By oxidizing the polysaccharide of Gastrodia elata stem to introduce aldehyde groups, and then grafting it with chitosan and chlorogenic acid to form a Schiff base cross-linking network, a stable hydrogel system is constructed, which enhances adhesion and sustained-release effect.

Benefits of technology

It reduces the frequency of hydrogel dressing changes, improves wound healing, enhances anti-inflammatory, antibacterial, and repair-promoting capabilities, and extends the lifespan of the dressing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121445941A_ABST
    Figure CN121445941A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogel, in particular to a hydrogel system based on oxidized gastrodia elata stem polysaccharide as well as a preparation method and application of the hydrogel system. The preparation method comprises the following steps: performing water extraction and alcohol precipitation treatment on gastrodia elata stems to obtain a gastrodia elata stem polysaccharide sample; the method comprises the following steps: carrying out oxidation treatment on a gastrodia elata stem polysaccharide sample by using sodium periodate, and introducing an aldehyde group into the gastrodia elata stem polysaccharide sample to obtain an oxidized gastrodia elata stem polysaccharide sample; activating chlorogenic acid by using an activating agent to obtain activated chlorogenic acid; the preparation method comprises the following steps: grafting chitosan and activated chlorogenic acid to obtain a graft of chitosan grafted chlorogenic acid; and carrying out Schiff base reaction on a cross-linking accelerant, the oxidized gastrodia elata stem polysaccharide sample and the graft of chitosan grafted chlorogenic acid to obtain the hydrogel system containing the oxidized gastrodia elata stem polysaccharide. According to the preparation method, the replacement frequency of a hydrogel system is reduced by optimizing the structural stability and long-acting moisturizing adhesiveness of the hydrogel, and meanwhile, the recovery effect of the hydrogel system is improved by virtue of the synergistic effect of various active components.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of hydrogel, in particular to a hydrogel system based on oxidized gastrodia elata stem polysaccharide and a preparation method and application thereof. BACKGROUND

[0002] Skin, as the largest immune defense line of the human body, needs to be exposed to the external environment for a long time. Once damaged by burns, scalds or infections, the skin is prone to be damaged. Traditional wound dressings, such as gauze, have the effect of hemostasis and ventilation, but gauze is easy to stick to the skin, and frequent replacement of gauze may also induce skin infection. In addition, in order to improve the antibacterial property of the dressing, an antibacterial drug generally needs to be added to the dressing. However, due to the problems of drug resistance and side effects of the antibacterial drug, the antibacterial drug has certain limitations. At present, nano drug carriers are widely used in wound treatment as a new emerging treatment method for wounds. Nano drug carriers encapsulate drugs in nanoparticles for release at the target site to improve the therapeutic effect of nano drug carriers. However, nano drug carriers are prone to decomposition, especially those carrying small molecules such as growth factors and proteins.

[0003] Hydrogel is a soft and elastic material and is widely used in wound dressings. Hydrogel generally has a three-dimensional structure, so that the hydrogel can closely adhere to the skin wound surface to maintain a moist environment for the skin wound, which is beneficial to the healing of the skin wound. In addition, hydrogel generally uses materials with good biocompatibility, so hydrogel is an ideal wound dressing. However, the hydrogel related dressings also need to be replaced frequently at present, and the recovery effect of the hydrogel dressing on the skin wound surface is limited. SUMMARY

[0004] The present application provides a hydrogel system based on oxidized gastrodia elata stem polysaccharide and a preparation method and application thereof, to solve the technical problem of how to reduce the replacement frequency of hydrogel dressing and improve the recovery effect of hydrogel dressing.

[0005] In a first aspect, the present application provides a preparation method of a hydrogel system based on oxidized gastrodia elata stem polysaccharide, which comprises: treating gastrodia elata stem with water extraction and alcohol precipitation to obtain a gastrodia elata stem polysaccharide sample; oxidizing the gastrodia elata stem polysaccharide sample with sodium periodate to introduce aldehyde groups into the gastrodia elata stem polysaccharide sample to obtain an oxidized gastrodia elata stem polysaccharide sample; activating the chlorogenic acid with an activating agent to obtain activated chlorogenic acid; grafting chitosan and the activated chlorogenic acid to obtain a graft of chitosan grafted chlorogenic acid; The Schiff base reaction is carried out on the crosslinking promoter, the oxidized Gastrodia elata stem polysaccharide sample and the graft of chlorogenic acid grafted chitosan to obtain a hydrogel system containing the oxidized Gastrodia elata stem polysaccharide.

[0006] Optionally, the mass m1 of the sodium periodate and the mass m2 of the Gastrodia elata stem polysaccharide sample satisfy: m1:m2=(2.5 to 3.5):1.

[0007] Optionally, the amount of substance n1 of the activator and the amount of substance n2 of the chlorogenic acid satisfy: n1:n2=(10 to 12):(2.8 to 3.0).

[0008] Optionally, the activator comprises N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and the amount of substance n3 of the N-hydroxysuccinimide and the amount of substance n4 of the 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride satisfy: n3:n4=(5 to 6):(5 to 6).

[0009] Optionally, the mass m3 of the oxidized Gastrodia elata stem polysaccharide sample, the mass m4 of the crosslinking promoter and the mass m5 of the graft satisfy: m3:m4:m5=12:1:(14 to 16).

[0010] Optionally, the crosslinking promoter comprises zinc chloride.

[0011] Optionally, the oxidation treatment time is ≥6h; and / or The grafting time is ≥24h.

[0012] In a second aspect, the embodiments of the present application provide a hydrogel system based on oxidized Gastrodia elata stem polysaccharide, which is prepared by the preparation method described in the first aspect.

[0013] Optionally, the hydrogel system comprises oxidized Gastrodia elata stem polysaccharide, and the amount of substance n5 of the aldehyde group in the oxidized Gastrodia elata stem polysaccharide and the mass m6 of the hydrogel system satisfy: n5:m6≥2.8×10 -3 :1, if the unit of n1 is mol, the unit of m6 is g.

[0014] In a third aspect, the embodiments of the present application provide a wound dressing, which comprises the hydrogel system described in the second aspect.

[0015] The above technical solutions provided by the embodiments of the present application have the following advantages compared with the prior art: The preparation method of the hydrogel system based on oxidized rhizoma gastrodiae stem polysaccharide provided by the embodiment of the application first carries out water sinking and alcohol extraction on the rhizoma gastrodiae stem, extracts a pure rhizoma gastrodiae stem polysaccharide sample, and then introduces aldehyde groups into the rhizoma gastrodiae stem polysaccharide sample by oxidizing the rhizoma gastrodiae stem polysaccharide sample with sodium periodate to form an oxidized rhizoma gastrodiae stem polysaccharide sample; the activated chlorogenic acid and chitosan are grafted to form a graft of chitosan and chlorogenic acid, under the action of a cross-linking promoter, the aldehyde groups of the oxidized rhizoma gastrodiae stem polysaccharide and the amino groups of the chitosan-grafted chlorogenic acid can undergo a Schiff base reaction to form a dynamic and stable cross-linking network, these cross-linking network structures can improve the mechanical properties of the hydrogel system, and fix the oxidized rhizoma gastrodiae stem polysaccharide and the chlorogenic acid, through the synergy of the oxidized rhizoma gastrodiae stem polysaccharide and the chlorogenic acid, the recovery effect of the hydrogel system can be improved, in addition, these cross-linking networks can prolong the retention time of the hydrogel auxiliary material on the wound, and reduce the frequent replacement caused by the failure of the hydrogel dressing. BRIEF DESCRIPTION OF DRAWINGS

[0016] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments consistent with the application and, together with the description, serve to explain the principles of the application.

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the application or the prior art, the accompanying drawings needed to be used in the embodiments or prior art description will be briefly introduced as follows. Obviously, those skilled in the art can obtain other drawings from these drawings without any creative effort.

[0018] Figure 1 A preparation method of a hydrogel system based on oxidized rhizoma gastrodiae stem polysaccharide provided by the embodiment of the application is shown in the flowchart; Figure 2 A hydrogel system based on oxidized rhizoma gastrodiae stem polysaccharide provided by the embodiment of the application is shown in the schematic diagram; Figure 3 A grafting mechanism diagram of activated chlorogenic acid and chitosan in the hydrogel system provided by the embodiment of the application is shown in the schematic diagram; Figure 4 A Schiff base reaction mechanism diagram of the oxidized rhizoma gastrodiae stem polysaccharide sample and the graft in the hydrogel system provided by the embodiment of the application is shown in the schematic diagram; Figure 5 A molecular weight distribution diagram of rhizoma gastrodiae stem polysaccharide provided by the embodiment of the application is shown in the schematic diagram; Figure 6 A monosaccharide composition diagram of rhizoma gastrodiae stem polysaccharide provided by the embodiment of the application is shown in the schematic diagram; Figure 7 Infrared spectrum diagrams of rhizoma gastrodiae stem polysaccharide and oxidized rhizoma gastrodiae stem polysaccharide provided by the embodiment of the application are shown in the schematic diagram; Figure 8The determination curve of aldehyde group concentration of oxidized Gastrodia elata stem polysaccharide provided by the embodiment of the present application, wherein, Figure 8 (a) is the titration curve of aldehyde group concentration of Gastrodia elata stem polysaccharide, Figure 8 (b) is the differential curve of aldehyde group concentration of Gastrodia elata stem polysaccharide, Figure 8 (c) is the titration curve of aldehyde group concentration of oxidized Gastrodia elata stem polysaccharide, Figure 8 (d) is the differential curve of aldehyde group concentration of oxidized Gastrodia elata stem polysaccharide; Figure 9 The infrared spectrum analysis comparison chart of chlorogenic acid, chitosan and grafting provided by the embodiment of the present application; Figure 10 The standard curve used for calculating the grafting rate of the grafting provided by the embodiment of the present application; Figure 11 The infrared spectrum comparison chart of hydrogel system of grafting with different mass concentrations provided by the embodiment of the present application; Figure 12 The X-ray photoelectron spectrogram of hydrogel system provided by the embodiment of the present application; Figure 13 The scanning electron microscope chart of hydrogel system under different magnifications provided by the embodiment of the present application, wherein, Figure 13 (a) is the scanning electron microscope chart of hydrogel system under 400 times magnification, Figure 13 (b) is the scanning electron microscope chart of hydrogel system under 500 times magnification, Figure 13 (c) is the scanning electron microscope chart of hydrogel system under 1000 times magnification, Figure 13 (d) is the scanning electron microscope chart of hydrogel system under 2000 times magnification; Figure 14 The adhesion experiment result chart of hydrogel system on different surfaces provided by the embodiment of the present application; Figure 15 The self-healing experiment result chart between different block hydrogel systems provided by the embodiment of the present application. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0020] The range descriptions described in the present application, such as numerical range, ratio range, etc., include all possible sub-ranges and single values within the range, for example, the range description of "1 to 6" or "1~6" covers all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms "comprise", etc. used herein mean "include but not limited to"; the relationship terms "first", "second", etc. are only used to distinguish different entities or operations, and do not imply actual sequence or relationship; "and / or" means that multiple cases can exist or coexist; "at least one", "multiple", "at least one" and the like refer to any combination of the corresponding objects, including single or multiple combinations of objects. The proportional relationship described in the text, such as mass ratio, molar ratio, etc., should be understood as the corresponding relationship between the front and rear terms of the proportion according to the description order. The raw materials, reagents, instruments and equipment used in the text can be purchased or prepared by existing methods.

[0021] It should be noted that Gastrodia elata stem polysaccharide (GEP) is composed of glucose, mannose and xylose and other monosaccharides. GEP has excellent water solubility and good biological activity. Existing research shows that GEP has antioxidant, anti-inflammatory and immune regulation functions. Its antioxidant capacity is about 20% higher than that of vitamin C. It has significant effects on skin moisturizing and anti-aging, can effectively reduce skin oxidative damage, and delay the aging process of the skin, so it is considered as an ideal skin care raw material. However, GEP belongs to a macromolecular structure, which leads to poor penetration of GEP into the deep layer of the skin, and GEP is prone to degradation in high temperature and light environments, which greatly limits its stability and long-term effect.

[0022] Chlorogenic acid (CA) is a natural phenolic compound with antioxidant, anti-inflammatory and antibacterial activity. CA can scavenge free radicals, reduce oxidative damage, and effectively inhibit the damage to the skin caused by ultraviolet light, and can also accelerate wound healing, which is of great benefit to skin health, so CA is widely used in skin care and wound repair fields. However, CA is strongly acidic, and if it is directly applied to the skin, it may damage the skin barrier, making the skin fragile and causing inflammatory reactions.

[0023] Chitosan (ECS) is a natural polysaccharide, ECS has good biocompatibility, degradable and antibacterial properties, and is widely used in drug delivery systems and hydrogel production. Existing studies have shown that the combination of ECS and GEP and other natural polysaccharides can prepare a composite hydrogel with strong adaptability to the skin, and the three-dimensional network structure of ECS can also strengthen the mechanical properties and stability of the hydrogel. The combination of ECS and CA not only enhances the stability of CA, but also improves the bioavailability of CA, reduces the degradation and failure of CA. Therefore, if the synergy of ECS, GEP and CA can be achieved, not only the sustained-release effect of GEP and CA can be improved, but also the service life of the hydrogel can be effectively prolonged.

[0024] Figure 1 An exemplary preparation method flowchart of a hydrogel system based on oxidized Gastrodia elata stem polysaccharide provided by the embodiments of the present application is shown; As Figure 1 shown, the preparation method of a hydrogel system based on oxidized Gastrodia elata stem polysaccharide provided by the embodiments of the present application comprises: S1. Water extraction and alcohol precipitation treatment is performed on Gastrodia elata stems to obtain a Gastrodia elata stem polysaccharide sample; S2. Sodium periodate is used to oxidize the Gastrodia elata stem polysaccharide sample to introduce aldehyde groups into the Gastrodia elata stem polysaccharide sample to obtain an oxidized Gastrodia elata stem polysaccharide sample; S3. An activating agent is used to activate the chlorogenic acid to obtain activated chlorogenic acid; S4. Chitosan and the activated chlorogenic acid are grafted to obtain a graft of chitosan grafted chlorogenic acid; S5. Schiff base reaction is performed on a cross-linking promoter, the oxidized Gastrodia elata stem polysaccharide sample and the graft of chitosan grafted chlorogenic acid to obtain a hydrogel system containing oxidized Gastrodia elata stem polysaccharide.

[0025] It should be noted that the preparation method of a hydrogel system based on oxidized Gastrodia elata stem polysaccharide provided by the embodiments of the present application optimizes the structural stability and long-lasting moisturizing and adhesive properties of the hydrogel to reduce the replacement frequency of the hydrogel system, and relies on the synergistic biological effects of multiple active ingredients to improve the recovery effect of the hydrogel system. The specific mechanism is as follows: I. Core mechanism of reducing the replacement frequency of the hydrogel system: The high replacement frequency of the hydrogel system is usually due to the defects of easy falling off of wound dressings, poor moisturizing property or easy degradation of the structure. The following two points are solved by the preparation method: 1. Schiff base reaction to construct a stable and long-acting hydrogel network: The aldehyde group of the oxidized gastrodia elata stem polysaccharide can have a Schiff base reaction with the amino group of the chitosan grafted chlorogenic acid, to form a dynamic and stable crosslinking network. These crosslinking networks not only can improve the mechanical strength of the hydrogel, and are not easy to be damaged or dissolved due to the activity of the wound surface or liquid soaking, but also can prolong the retention time of the hydrogel system on the wound surface, and reduce the frequent replacement caused by the failure of the hydrogel system; 2. Enhancing the moisturizing property and adhesion of the hydrogel: The gastrodia elata stem polysaccharide itself has strong water absorption and water retention capacity, and after oxidation treatment, the hydrophilic skeleton of the polysaccharide is still retained, which can continuously provide a moist environment for the wound surface, avoiding the need for early replacement due to dryness and dressing clumping of the wound surface; The chitosan has excellent biological adhesion, and after grafting with chlorogenic acid, it can closely adhere to the skin of the wound surface, and is not easy to fall off due to the activity of the limbs, further reducing the unnecessary replacement operation.

[0026] II. Core mechanism of improving the recovery effect of the hydrogel system The recovery effect depends on the comprehensive effect of anti-inflammatory, antibacterial and promoting repair of the wound surface, which is realized by the synergistic effect of active ingredients + slow release: 1. Synergistic biological activity of chlorogenic acid and chitosan: After activation and grafting, the chlorogenic acid can stably retain its anti-inflammatory and antioxidant properties, which can reduce the inflammatory response of the wound surface, reduce problems such as redness and exudation, and create a good environment for tissue repair; Chitosan itself has broad-spectrum antibacterial properties, which can inhibit the growth of related bacteria on the wound surface and reduce the risk of infection; at the same time, chitosan can promote the proliferation of fibroblasts and accelerate the growth of granulation tissue, directly promoting wound healing; 2. Nutritional support and slow release effect of oxidized gastrodia elata stem polysaccharide: The polysaccharide chain of the oxidized gastrodia elata stem polysaccharide can provide nutrition for the repair cells of the wound surface, and the crosslinking network of the hydrogel can slowly release active ingredients such as chlorogenic acid and chitosan, avoiding the rapid loss of active substances, so that the repair effect of the hydrogel system can continuously act on the wound surface, improving the healing efficiency.

[0027] In summary, the preparation method of the hydrogel system based on the oxidized gastrodia elata stem polysaccharide provided by the embodiment of the application, the preparation method is to modify the gastrodia elata stem polysaccharide by oxidation to form an oxidized gastrodia elata stem polysaccharide sample, then graft chlorogenic acid and chitosan to form a grafting product, and finally crosslink the grafting product and the oxidized gastrodia elata stem polysaccharide sample through a Schiff base reaction to form a crosslinking network. These crosslinking networks can fix the oxidized gastrodia elata stem polysaccharide sample and the chlorogenic acid, promote the synergy between them, improve the recovery effect of the hydrogel system, and promote the close combination of the hydrogel system and the wound surface, thereby reducing the replacement frequency of the hydrogel system.

[0028] In some optional embodiments, the mass m1 of the sodium periodate and the mass m2 of the Gastrodia stem polysaccharide sample satisfy: m1:m2= (2.5 to 3.5):1.

[0029] In these embodiments, the sodium periodate and the Gastrodia stem polysaccharide sample in a mass ratio of (2.5 to 3.5):1 can facilitate the oxidation process to proceed sufficiently, so that sufficient aldehyde groups are introduced into the Gastrodia stem polysaccharide sample, which can react with the amino groups of the graft in the subsequent Schiff base reaction to form a complex crosslinking network, so as to fix the oxidized Gastrodia stem polysaccharide sample and the chlorogenic acid and improve the bonding degree of the hydrogel system to the wound surface.

[0030] The mass m1 of the sodium periodate can be 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, or 3.5.

[0031] In some optional embodiments, the amount of substance n1 of the activator and the amount of substance n2 of the chlorogenic acid satisfy: n1:n2= (10 to 12):(2.8 to 3.0).

[0032] In these embodiments, the activator and the chlorogenic acid in a mass ratio of (10 to 12):(2.8 to 3.0) can facilitate the activation process to proceed sufficiently, so that the surface groups of the chlorogenic acid can be activated by activation, which is conducive to the subsequent grafting of the activated chlorogenic acid and chitosan to form a tight chitosan and chlorogenic acid graft.

[0033] The amount of substance n1 of the activator can be 10, 10.5, 11, 11.5, or 12.0.

[0034] The amount of substance n2 of the chlorogenic acid can be 2.8, 2.85, 29, 2.95, 3.00.

[0035] In some optional embodiments, the activator comprises: N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, the amount of substance n3 of the N-hydroxysuccinimide and the amount of substance n4 of the 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride satisfy: n3:n4= (5 to 6):(5 to 6).

[0036] In these embodiments, the use of N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride as activators in a mass ratio of (5 to 6):(5 to 6) can effectively activate the chlorogenic acid, activate the chlorogenic acid groups, and facilitate the chlorogenic acid to graft with chitosan effectively to form a chlorogenic acid and chitosan graft, which is conducive to the subsequent Schiff base reaction.

[0037] The value of the amount of substance n3 of the N-hydroxysuccinimide can be 5, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, or 6.0.

[0038] The value of the amount of substance n4 of the 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride can be 5, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, or 6.0.

[0039] In some optional embodiments, the mass m3 of the oxidized Gastrodia elata stem polysaccharide sample, the mass m4 of the cross-linking promoter, and the mass m5 of the graft satisfy: m3:m4:m5=12:1:(14 to 16).

[0040] In these embodiments, the oxidized Gastrodia elata stem polysaccharide sample, the cross-linking promoter, and the graft with a mass ratio of 12:1:(14 to 16) can make the Schiff base reaction proceed sufficiently, so that the graft and the oxidized Gastrodia elata stem polysaccharide sample are cross-linked to form cross-linking networks, which can fix the oxidized Gastrodia elata stem polysaccharide sample and the chlorogenic acid, promote the synergy between the two, improve the recovery effect of the hydrogel system, and promote the close combination of the hydrogel system and the wound surface, thereby reducing the replacement frequency of the hydrogel system.

[0041] The value of the mass m5 of the graft can be 14, 14.1, 14.2, 14.3, 14.4, 14.5, 15.0, 15.5, or 16.0.

[0042] In some optional embodiments, the cross-linking promoter comprises zinc chloride.

[0043] In these embodiments, the use of zinc chloride as the cross-linking promoter can promote the Schiff base reaction between the graft and the oxidized Gastrodia elata stem polysaccharide sample to proceed sufficiently, and form cross-linking networks, which can fix the oxidized Gastrodia elata stem polysaccharide sample and the chlorogenic acid, promote the synergy between the two, improve the recovery effect of the hydrogel system, and promote the close combination of the hydrogel system and the wound surface, thereby reducing the replacement frequency of the hydrogel system.

[0044] In some optional embodiments, the oxidation treatment time is ≥6h; and / or The grafting time is ≥24h.

[0045] In these embodiments, the oxidation treatment for ≥6h can make the activator activate the chlorogenic acid sufficiently to form activated chlorogenic acid; in addition, the grafting for ≥24h can make the activated chlorogenic acid and the chitosan react sufficiently and form the graft.

[0046] Figure 2A schematic diagram of the hydrogel system based on oxidized rhizoma gastrodiae stem polysaccharide provided by the embodiment of the application is exemplarily shown; Based on a general inventive concept, as Figure 2 The hydrogel system based on oxidized rhizoma gastrodiae stem polysaccharide provided by the embodiment of the application is prepared by the preparation method.

[0047] The hydrogel system is based on the preparation method described above, and the specific steps of the preparation method can be referred to the above embodiment. Since the hydrogel system adopts part or all of the technical solutions of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment, which will not be repeated here.

[0048] It should be noted that the two-dimensional plane structure of chlorogenic acid (CAS NO: 327-97-9) and chitosan (CAS NO: 9012-76-4) is obtained through the CHEM LINK database (http: / / www.Chemblink.com / asp / searching.asp), and the structure of rhizoma gastrodiae stem polysaccharide is determined through existing literature. Through analysis of these structure diagrams, the specific formation mechanism of the hydrogel system can be determined: (1) the grafting mechanism of activated chlorogenic acid and chitosan: as shown in Figure 3 The carboxyl group in the activated chlorogenic acid molecule forms an active intermediate (O-acyl urea intermediate) with 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl), which further generates a more stable N-succinimidyl ester intermediate with N-hydroxysuccinimide (NHS). The N-succinimidyl ester intermediate has higher activity. The amino group (-NH2) in the chitosan molecule attacks the N-succinimidyl ester intermediate to replace the NHS, forming an amide bond (-CONH-), and completing the grafting reaction. (2) The Schiff base reaction mechanism of oxidized rhizoma gastrodiae stem polysaccharide sample and graft: although rhizoma gastrodiae stem polysaccharide itself can react with the amino group of chitosan in the graft to form a Schiff base, the aldehyde group of rhizoma gastrodiae stem polysaccharide is less, which makes the Schiff base reaction activity poor. Therefore, the rhizoma gastrodiae stem polysaccharide is oxidized by sodium periodate, as shown in Figure 4 The adjacent diol structure in the rhizoma gastrodiae stem polysaccharide molecule is broken to generate more aldehyde groups, enhancing the Schiff base reaction activity of oxidized rhizoma gastrodiae stem polysaccharide and the graft. The aldehyde group in the oxidized rhizoma gastrodiae stem polysaccharide reacts with the amino group of chitosan to form a carbon-nitrogen double bond (-C=N-); in addition, the zinc ion in the cross-linking promoter zinc chloride can coordinate with the amino group of chitosan in the graft, the aldehyde group of oxidized rhizoma gastrodiae stem polysaccharide or other oxygen atoms with lone pair electrons, further enhancing the cross-linking degree between oxidized rhizoma gastrodiae stem polysaccharide and chitosan, and forming a three-dimensional network structure, finally forming a hydrogel system rich in cross-linked network.

[0049] In some optional embodiments, the hydrogel system comprises oxidized Gastrodia elata stem polysaccharide, wherein the amount of aldehyde groups n5 in the oxidized Gastrodia elata stem polysaccharide and the mass m6 of the hydrogel system satisfy: n5:m6 ≥ 2.8 × 10⁻⁶. -3 :1. If the unit of n1 is mol, then the unit of m6 is g.

[0050] In these embodiments, the amount of substance and the mass of the hydrogel system satisfy: n5:m6 ≥ 2.8 × 10⁻⁶ -3 The aldehyde groups in the oxidized Gastrodia elata stem polysaccharide of 1 can provide sufficient aldehyde groups in the hydrogel system, indicating that the hydrogel system has a sufficient cross-linking network. These cross-linking networks can fix the oxidized Gastrodia elata stem polysaccharide sample and chlorogenic acid, promote synergy between the two, improve the recovery effect of the hydrogel system, and promote the close binding of the hydrogel system with the wound surface, reducing the frequency of hydrogel system replacement.

[0051] Based on a general inventive concept, embodiments of this application provide a wound dressing comprising the hydrogel system.

[0052] The wound dressing is based on the above-described hydrogel system. The specific composition of the hydrogel system can be referred to in the above embodiments. Since the wound dressing adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be elaborated here.

[0053] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national / industry standards; if there is no corresponding national / industry standard, they are performed according to general international standards, conventional conditions, or conditions recommended by the manufacturer.

[0054] Example 1

[0055] The raw materials and their sources used in this embodiment are shown in Table 1.

[0056] Table 1. Raw materials and sources of Example 1

[0057] The equipment information used in this embodiment is shown in Table 2.

[0058] Table 2. Experimental equipment information for Example 1

[0059] like Figure 1 As shown, a method for preparing a hydrogel system based on oxidized Gastrodia elata stem polysaccharide is disclosed. The preparation method includes: S1. The Gastrodia elata stem is subjected to water extraction and alcohol precipitation to obtain a Gastrodia elata stem polysaccharide sample; the specific steps are as follows: Fresh Gastrodia elata stems are dried at 45°C until the weight is constant to obtain Gastrodia elata stem solid phase material; the Gastrodia elata stem solid phase material is then crushed and passed through a 40-mesh screen to obtain Gastrodia elata stem powder; the Gastrodia elata stem powder is soaked in anhydrous ethanol at 30 times the volume of the Gastrodia elata stem powder overnight to achieve decolorization and removal of alcohol-soluble impurities, thereby obtaining pure Gastrodia elata stem raw material; Deionized water is added at a mass-to-volume ratio of 1 g:30 mL of the pure Gastrodia elata stem raw material, and the mixture is stirred at 90°C for 2 h, repeated twice, and the extract is combined to obtain a Gastrodia elata stem solution; The Gastrodia elata stem solution is subjected to oscillation for 20 min by the Sevage method (using chloroform and n-butanol at a volume ratio of 4:1 as the extraction agent), then centrifuged, repeated multiple times until no absorption is detected at 280 nm under ultraviolet light, a total of 5 times, to obtain a deproteinized Gastrodia elata stem solution; Under stirring, 95% ethanol solution is slowly added to the deproteinized Gastrodia elata stem solution until the volume fraction of the ethanol solution reaches 80%, and then the mixture is allowed to stand at 4°C for 12 h to obtain an alcohol-extracted Gastrodia elata stem polysaccharide solution; The alcohol-extracted Gastrodia elata stem polysaccharide solution is subjected to centrifugal treatment to obtain a Gastrodia elata stem polysaccharide crude product; The Gastrodia elata stem polysaccharide crude product is redissolved, and then the redissolved solution is subjected to running water dialysis for 48 h using a 3.5 kDa dialysis bag to obtain a Gastrodia elata stem polysaccharide dialysate; The Gastrodia elata stem polysaccharide dialysate is freeze-dried to obtain a white flocculent Gastrodia elata stem polysaccharide sample GEP.

[0060] S2. The Gastrodia elata stem polysaccharide sample is subjected to oxidation treatment using sodium periodate to introduce aldehyde groups into the Gastrodia elata stem polysaccharide sample to obtain an oxidized Gastrodia elata stem polysaccharide sample; the specific steps are as follows: 3 g of the Gastrodia elata stem polysaccharide sample GEP is weighed and dissolved in 450 mL of purified water to obtain a Gastrodia elata stem polysaccharide sample solution; 7.5 g of sodium periodate is added to the Gastrodia elata stem polysaccharide sample solution, and the mixture is subjected to oxidation treatment under light shielding conditions for 6 h, then an appropriate amount of ethylene glycol is added and stirred, and the oxidation treatment is terminated after a period of time to obtain an oxidized Gastrodia elata stem polysaccharide crude product; The oxidized Gastrodia elata stem polysaccharide crude product is subjected to dialysis for 72 h using a 7000 Da dialysis bag to obtain an oxidized Gastrodia elata stem polysaccharide dialysate; the oxidized Gastrodia elata stem polysaccharide dialysate is then freeze-dried to obtain an oxidized Gastrodia elata stem polysaccharide (OGEP); S3. The chlorogenic acid is activated using an activating agent to obtain activated chlorogenic acid; the specific steps are as follows: Take 1.15g of EDC·HCl, dissolve in 25mL of anhydrous ethanol, then add 0.69g of NHS to the anhydrous ethanol solution, then add 1.06g of chlorogenic acid for activation to obtain activated chlorogenic acid.

[0061] S4. Grafting chitosan and activated chlorogenic acid to obtain the graft of chitosan grafted chlorogenic acid; specific steps: Weigh 1.01g of chitosan, dissolve the chitosan in 100mL of 1% acetic acid solution, and stir at 25℃ for 1h to obtain a chitosan solution. Add the chitosan solution to the activated chlorogenic acid dropwise, and graft at room temperature for 24h to obtain the primary graft of chitosan grafted chlorogenic acid; Use a 7000Da dialysis bag to dialyze the primary graft product for 3d to obtain a graft dialysate; Freeze-dry the graft dialysate to obtain the graft of chitosan grafted chlorogenic acid (ECS-CA).

[0062] S5. Schiff base reaction of crosslinking promoter, oxidized Gastrodia elata stem polysaccharide sample and graft of chitosan grafted chlorogenic acid to obtain a hydrogel system containing oxidized Gastrodia elata stem polysaccharide; specific steps: Prepare a 15mg / mL ECS-CA solution, and dissolve OGEP in water to form a 20mg / mL OGEP solution. Add 1mL of the ECS-CA solution to a small glass bottle and stir, then slowly add 50μL of a 20mg / mL ZnCl2 solution, then slowly add 0.6mL of a 20mg / mL OGEP solution, and stir uniformly to perform Schiff base reaction to obtain a hydrogel.

[0063] Example 2

[0064] Compared with Example 1, the differences of Example 2 are as follows, and the rest are the same: The mass m1 of sodium periodate and the mass m2 of Gastrodia elata stem polysaccharide sample satisfy: m1:m2=2.5:1.

[0065] The amount of substance n1 of the activator and the amount of substance n2 of chlorogenic acid satisfy: n1:n2=10:2.9.

[0066] The amount of substance n3 of N-hydroxysuccinimide and the amount of substance n4 of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride satisfy: n3:n4=5:5.

[0067] Example 3

[0068] Compared with Example 1, the differences of Example 3 are as follows, and the rest are the same: The mass m1 of sodium periodate and the mass m2 of the Gastrodia stem polysaccharide sample satisfy: m1:m2=3.5:1.

[0069] The amount of substance n1 of the activator and the amount of substance n2 of the chlorogenic acid satisfy: n1:n2=12:2.8.

[0070] The amount of substance n3 of N-hydroxysuccinimide and the amount of substance n4 of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride satisfy: n3:n4=5.5:5.5.

[0071] Comparative Example 1 Comparative Example 1 is different from Example 1 as follows, and the rest are the same: The Gastrodia stem polysaccharide sample is not subjected to oxidation treatment, and the Gastrodia stem polysaccharide sample is directly used to react with the graft to form a hydrogel product.

[0072] Comparative Example 2 Comparative Example 1 is different from Example 1 as follows, and the rest are the same: The mass concentration of the ECS-CA solution is 5 mg / mL, 10 mg / mL, and 20 mg / mL.

[0073] Related experiments and effect data: 1. Characteristic distribution of Gastrodia stem polysaccharide: (1) Infrared spectrum characteristic distribution of Gastrodia stem polysaccharide: In Example 1, Fourier transform infrared spectrometer was used to test the infrared spectrum of Gastrodia stem polysaccharide, potassium bromide was used as the bottom plate, and the scanning range was 400 cm -1 to 4000 cm -1 . As shown in Figure 6 , the infrared spectrum of the extracted Gastrodia stem polysaccharide shows characteristic absorption peaks at 3436 cm -1 , 2930 cm -1 , and 1733 cm -1 , and the characteristic absorption peak at 1733 cm -1 corresponds to the asymmetric stretching vibration of the carbonyl group (C=O) in the uronic acid, which indicates that the oxidized Gastrodia stem polysaccharide contains uronic acid components; (2) Molecular weight distribution (GPC-RI) of Gastrodia stem polysaccharide: Instrument and conditions: Shimadzu LCsolution + RID-10A was used; the mobile phase was 0.2 M NaCl, the flow rate was 0.5 mL / min, and the determination temperature was 35℃; Pullulan calibration was performed. As shown in Figure 5 , the Gastrodia stem polysaccharide is a narrow-distribution medium-low molecular weight polysaccharide with a weight average molecular weight of about 10.6 kDa, equivalent to 60 to 70 hexose residues. Figure 5The small peak at 15.6 min is due to the residual free monosaccharides or buffer salts after TFA hydrolysis and can be ignored; (3) Monosaccharide composition (PMP-HPLC, 250 nm): Hydrolysis and derivatization: Neutralization was performed using 2M TFA at 105℃ for 6 h, followed by reaction with PMP at 70℃ for 90 min. Separation was then performed using a C18 (250×4.6 mm, 5µm) separator. The mobile phase was 0.05M KH₂PO₄:CH₃CN = 80:20; the flow rate was 1 mL / min; and the flow conditions were 35℃. Results are as follows: Figure 6 As shown, the main components of Gastrodia elata stem polysaccharide are glucose (Glc), mannose (Man), galactose (Gal), rhamnose (Rha), galacturonic acid (GalA), and arabinose (Ara), with glucose and mannose being the most abundant. The monosaccharide molar ratio of Gastrodia elata stem polysaccharide is Glc:Man:Gal:Rha:Ara = 1.00:0.08:0.04:0.02:0.008.

[0074] 2. Infrared spectral characteristics of Gastrodia elata stem polysaccharide and oxidized Gastrodia elata stem polysaccharide: Equal amounts of Gastrodia elata stem polysaccharide and oxidized Gastrodia elata stem polysaccharide were analyzed by infrared spectroscopy, and the results are as follows: Figure 7 As shown, by Figure 7 It can be seen that the infrared spectra of Gastrodia elata stem polysaccharide and oxidized Gastrodia elata stem polysaccharide are similar, both showing a value of 3436 cm⁻¹. -1 2930cm -1 and 1733cm -1 Characteristic absorption peaks, and 3436 cm⁻¹ -1 2930cm -1 The characteristic absorption peaks are related to the stretching vibrations of OH and CH in Gastrodia elata stem polysaccharide, respectively, while the 1733 cm⁻¹ peak is related to these vibrations. -1 The characteristic absorption peak corresponds to the asymmetric stretching vibration of the carbonyl group (C=O) in uronic acid, indicating that both Gastrodia elata stem polysaccharide and oxidized Gastrodia elata stem polysaccharide contain uronic acid components, but the 1733 cm⁻¹ peak of oxidized Gastrodia elata stem polysaccharide is different. -1 The strong intensity of the characteristic absorption peak indicates that the oxidized Gastrodia elata stem polysaccharide after oxidation treatment contains more uronic acid groups.

[0075] 3. The OGEP obtained in Example 1 was subjected to determination of its aldehyde concentration. The specific procedure is as follows: The degree of oxidation of OGEP was determined by the hydroxylamine hydrochloride method: (1) Preparation of 0.1 mol / L NaOH titration solution: Weigh 0.2 g of sodium hydroxide and dissolve it in 50 mL of water to form NaOH titration solution; (2) Preparation of 0.25 mol / L hydroxylamine hydrochloride solution: 0.435 g of hydroxylamine hydrochloride was weighed and dissolved in 3.75 mL of water, then 0.15 mL of 0.5% methyl orange solution was added, and finally diluted to 25 mL to obtain a 0.25 mol / L hydroxylamine hydrochloride solution; (3) 0.05 g of OGEP was weighed and added to 12.5 mL of 0.25 mol / L hydroxylamine hydrochloride solution, mixed uniformly to obtain the test solution; the test solution was titrated using NaOH titration solution, and the amount of HCl released in the test solution was determined by potentiometric titration, then the amount of NaOH used for titration was calculated to obtain the mass concentration of aldehyde groups in OGEP.

[0076] Since the amino group in hydroxylamine hydrochloride is very active and can easily react with the aldehyde groups in GEP and OGEP to form oxime compounds and release hydrogen chloride, the released HCl can be determined by neutralization reaction with NaOH titration solution. With the addition of NaOH titration solution, the pH value of the test solution gradually increases. Record the relationship between the volume of NaOH titration solution and the pH value of the test solution until the color of the test solution changes from red to yellow, and stop titrating the NaOH titration solution. Take the volume of NaOH titration solution V as the horizontal coordinate and the pH value as the vertical coordinate, and plot the titration curve of pH vs. the volume of NaOH titration solution in OriginPro 7.5 software, as shown in Figure 8 (a) and Figure 8 (c). Then, the titration curve is differentiated once to obtain the differential curve, as shown in Figure 8 (b) and Figure 8 (d), and the peak value corresponds to the volume of NaOH titration solution consumed at the end point of titration. Finally, the aldehyde group concentration of oxidized GEP ([CHO], unit: mol / g) can be calculated by formula 1 and formula 2: V 差 ×0.01×n NaOH =n CHO , formula 1; [CHO]=n CHO / m OGEP , formula 2; In formula 1 and formula 2, V 差 is the volume of NaOH titration solution consumed during titration, unit: mL; n NaOH is the molar concentration of NaOH, unit: mol / L; n CHO is the number of moles of aldehyde groups in OGEP; and m OGEP is the mass of oxidized GEP, unit: g. Substitute the measured data into formula 1 and formula 2 to calculate nCHO=(1.6-0.2)×0.001×0.1 =1.4×10-4 mol; [CHO] = 1.4 × 10 -4 / 0.05=2.8×10 -3 mol / g.

[0077] Based on the above calculation formula, the concentration of aldehyde groups in the Gastrodia elata stem polysaccharide of Comparative Example 1 was determined to be 7.6 × 10⁻⁶. -3 mol / g.

[0078] 4. Infrared spectral analysis of chitosan grafts with activated chlorogenic acid: Infrared spectroscopy of the graft was performed using a Fourier transform infrared spectrometer with potassium bromide as the film and a scanning range of 400 cm⁻¹. -1 Up to 4000cm -1 The characteristic absorption peaks of ECS, ECS-CA, and CA are clearly presented. The results are as follows... Figure 9 As shown, at 3447cm -1 2923cm -1 2870cm -1 1652cm -1 1602cm -1 1070cm -1 These characteristic absorption peaks correspond to the characteristic absorption peaks of different functional groups. Among them, 3447 cm⁻¹ -1 The characteristic absorption peak is attributed to the stretching vibrations of the -OH and -NH groups, 2923 cm⁻¹. -1 2870cm -1 The characteristic absorption peaks are the symmetric and asymmetric stretching vibrations of -CH, at 1652 cm⁻¹. -1 The characteristic absorption peak is due to the stretching vibration of C=O, at 1602 cm⁻¹. -1 The characteristic absorption peak corresponds to the NH bending vibration, 1070 cm⁻¹ -1 The characteristic absorption peaks correspond to the stretching vibrations of the CO skeleton. The group characteristics corresponding to these characteristic absorption peaks are highly consistent with the properties of ECS as a polysaccharide. Furthermore, in the infrared spectrum of ECS-CA, in addition to retaining the original characteristic peaks of ECS, a new peak appears at 1528 cm⁻¹. -1 and 813cm -1 A new absorption peak appeared at 3500 cm⁻¹. Analysis revealed that these two characteristic peaks originated from the CH bending vibration of the benzene ring structure and the CH symmetry vibration of the benzene ring, respectively. This strongly suggests that the CA molecule participated in the grafting reaction. Compared to ECS, the ECS-CA copolymer showed a higher absorption peak at 3500 cm⁻¹. -1 Up to 3000cm -1The characteristic absorption peaks in this wave number range appeared attenuation and broadening, which was most likely due to the introduction of CA, so that the free N-H and O-H stretching vibration was disturbed. In addition, the infrared spectrum of ECS-CA grafting also had two obvious changes, one was the disappearance of the characteristic absorption peak at 1652 cm -1 , the second was the broadening of the characteristic absorption peak at 1602 cm -1 . It was speculated that the amino group in ECS reacted with the carboxyl group in CA, and then formed an amide bond (-C=O-NH-). At the same time, in the infrared spectrum of ECS-CA copolymer, a new characteristic absorption peak at 1684 cm -1 appeared, which corresponded to the stretching vibration of C-O-C group, fully indicating that the hydroxyl group on ECS and the carboxyl group on CA successfully formed an ester bond.

[0079] Finally, in the infrared spectrum of CA, the two characteristic absorption peaks at 1528 cm -1 and 813 cm -1 again clearly appeared, further confirming the existence of CA in the copolymer, and providing strong evidence for the fact that CA participated in the copolymerization reaction. Therefore, according to Figure 9 , it can be determined that the grafting reaction of ECS and CA is not simply combined by physical action, but successfully synthesizes CA-ECS grafting through covalent bond (amide bond and ester bond).

[0080] 5. Calculation of the grafting rate of the grafting product: the polyphenol content in ECS-CA was determined by Folin-Ciocalteu method: (1) The Folin-Ciocalteu reagent was diluted 10 times with distilled water before use; (2) Preparation of the control solution: accurately weigh 10.08 mg of gallic acid, dissolve it in an appropriate amount of water, and transfer it to a 10 mL volumetric flask. Add water to the mark to make a gallic acid control stock solution with a concentration of 1 mg / mL; (3) Preparation of the test solution: respectively weigh 10 mg of ECS-CA and ECS, and place them in a 10 mL volumetric flask. Add an appropriate amount of water, then ultrasonic treat the volumetric flask for 10 min to make it completely dissolved. After cooling, continue to add water to the mark to obtain the final test solution; (4) Draw the standard curve: take 1000 μL of gallic acid control product stock solution, pour into a 10 mL volumetric flask, and add water to the mark, to get a concentration of 100 μg / mL standard solution. Then the standard solution is diluted into different concentrations (100 μg / mL, 80 μg / mL, 60 μg / mL, 40 μg / mL, 20 μg / mL, 0 μg / mL) of control solution by stepwise dilution method. Then accurately take 0.5 mL of gallic acid control product solution of different concentrations into test tubes. Add 3.5 mL of diluted Folin-Ciocalteu reagent to each test tube, mix well and stand for 5 min. And add 2.5 mL of 7.5% sodium carbonate solution, mix well, and put the test tubes in a 30°C water bath for 30 min, while gently shaking the test tube. After the reaction is completed, take out the test tube, cool to room temperature, and use a spectrophotometer to measure the absorbance at 760 nm wavelength. Draw the standard curve by the absorbance and the data of different concentrations of standard solution; (5) Determination of samples: take 0.5 mL of the sample solution, follow the same method as drawing the standard curve, add reagents and react for 30 min, and use a spectrophotometer to measure the absorbance value at 760 nm wavelength. Through the standard curve drawn, use the regression equation of absorbance value and concentration to calculate the total polyphenol content in the sample.

[0081] The results are shown in Figure 10 The regression equation y = 0.009x + 0.0187 (where y is the absorbance and x is the concentration of gallic acid) is obtained by drawing the standard curve of gallic acid control solution. The R 2 = 0.9955 of the standard curve, indicating that the fitting degree of the standard curve is good and the equation is highly reliable. The absorbance values of ECS and ECS-CA are 0.048 and 0.261 respectively, which are substituted into the regression equation to calculate the corresponding concentrations. The difference between the two concentrations is 23.67 μg / mL, which reflects the change in the concentration of the system after grafting chlorogenic acid. The grafting rate is obtained by dividing the concentration difference by the corresponding concentration (0.1 mg / mL), which is 23.67%. This shows that ECS has successfully grafted a certain amount of chlorogenic acid, reflecting that chitosan and chlorogenic acid have a certain degree of grafting reaction.

[0082] 5. Structure characterization of hydrogel system: (1) Surface morphology of hydrogel system: yellow-green jelly-like colloid; (2) Flowability test of the hydrogel system: The hydrogel systems prepared with different concentrations of ECS-CA in Example 1 and Comparative Example 2 were placed in transparent glass bottles, the bottles were sealed, and then the bottles were immediately inverted to observe the flow of the hydrogel and determine its gel strength. The results showed that the mechanical properties of the hydrogel system were significantly correlated with the mass concentration of ECS-CA. When the mass concentration of ECS-CA was 10 mg / mL, the hydrogel system showed obvious flowability after inversion, quickly migrating to the mouth of the glass bottle and leaving sliding traces on the bottle wall. This indicates that the crosslinking density of the hydrogel system was insufficient at this time, and the three-dimensional network structure had not been fully formed, resulting in a storage modulus lower than the loss modulus, which could not resist gravitational deformation. When the ECS-CA concentration was increased to 15 mg / mL, the inverted sample in the glass bottle maintained a stable morphology without flow. This indicates that the 15 mg / mL ECS-CA concentration formed a gel network with sufficient elastic modulus, with the storage modulus significantly exceeding the loss modulus. The gel point of the hydrogel system had reached the critical crosslinking threshold, indicating that the solid-like structure of the hydrogel system had been successfully and stably constructed. However, when the ECS-CA concentration was further increased to 20 mg / mL, the hydrogel system exhibited uneven aggregation and could not effectively spread into a film. This may be due to excessive entanglement between excessive polymer chains in the hydrogel leading to phase separation, or excessively strong electrostatic interactions causing localized aggregation, resulting in the hydrogel system losing its homogeneous gel properties. Therefore, through gradient mass concentration experiments with ECS-CA, it can be clearly determined that 15 mg / mL represents ECS-CA / OGEP / Zn. 2+ The optimal mass concentration for hydrogel system molding.

[0083] (3) Infrared spectroscopy of the hydrogel system was performed using a Fourier transform infrared spectrometer: Hydrogel systems using ECS-CA at different mass concentrations showed almost identical infrared spectra. However, the results from... Figure 11 As shown, several characteristic absorption peaks can be observed in the ECS-CA hydrogel systems with different mass concentrations. Among them, the peak at 34479 cm⁻¹ is particularly prominent. -1 The characteristic absorption peak is mainly attributed to the stretching vibrations of OH and NH, indicating that the OGEP molecule is rich in hydroxyl groups, while the ECS molecule contains amino groups. Furthermore, at 29309 cm⁻¹... -1 The characteristic absorption peak originates from the stretching vibration of the CH bond, reflecting the characteristics of saturated hydrocarbon groups in OGEP and ECS molecules. For the OGEP molecule, 17339 cm⁻¹ is the peak value. -1 The characteristic absorption peak is related to the stretching vibration of C=O, further confirming the presence of a carboxyl group in the molecular structure of OGEP. In hydrogel systems with different mass concentrations of ECS-CA, the 1645 cm⁻¹ peak... -1A new absorption peak was observed at each location, which was mainly caused by the formation of Schiff base bonds. The appearance of this characteristic absorption peak indicates that a hydrogel system was successfully formed between OGEP and ECS-CA through a Schiff base reaction.

[0084] (4) X-ray photoelectron spectroscopy (XPS): X-ray photoelectron spectroscopy was used to analyze the surface elemental composition of the hydrogel system. The elements present in the hydrogel system, along with their mass and atomic fractions, were identified by the positions of characteristic peaks in the spectra. This allowed for the analysis of changes in the proportion of functional groups and verification of chemical bond formation during the hydrogel preparation process. The results are as follows: Figure 12 As shown in the figure, the XPS spectrum of the hydrogel system confirms that the hydrogel system has been successfully prepared, and the elemental composition of the hydrogel system exhibits a specific pattern: carbon dominates the hydrogel system, accounting for 52.88% by weight and 64.64% by atomic percentage; oxygen accounts for 35.23% by weight and 32.33% by atomic percentage; while the contents of zinc and nitrogen are relatively small, with zinc accounting for 11.45% by weight and only 2.57% by atomic percentage, and nitrogen accounting for 0.44% by weight and 0.46% by atomic percentage.

[0085] Therefore, the characteristic peaks in the XPS spectra indicate that the hydrogel system is mainly composed of carbon, nitrogen, oxygen, and zinc. A weak peak at 84 eV is observed in the XPS spectrum, attributed to the electronic transition of the CO bond, while a main peak appears at the O 1s position, corresponding to a binding energy of 530 eV, originating from the oxygen group. The XPS spectrum of Zn 2p indicates that Zn... 2+ The weight content was 11.45%, and a distinguishable peak was observed at 1019 eV. Simultaneously, a peak appeared in N1s at 398 eV, which is attributed to the change in the electronic environment of the nitrogen atom due to coordination bonds, strongly confirming the formation of coordination bonds in the hydrogel system.

[0086] (5) Scanning electron microscopy (SEM): The hydrogel system was rapidly frozen and fractured in liquid nitrogen, then dried using a freeze dryer. The fracture surface of the hydrogel system was then sputter-coated with gold, and the morphological characteristics of the fracture surface were observed using a scanning electron microscope. Figure 13 (a) Figure 13 As shown in (b), at lower magnifications, the hydrogel system exhibits a uniform three-dimensional porous network structure with relatively uniform and interconnected pore distribution. This may be due to the physical cross-linking of OGEP and ECS-CA and the presence of Zn. 2+ A stable framework formed by coordination. For example... Figure 13 (c) Figure 13(d) As shown, under high magnification, the fiber crosslinking structure of the hydrogel system leads to a higher surface roughness of the hydrogel system, and there are more fine textures and branch structures on the surface of the pore wall. The gaps between fibers form secondary pores, which significantly increase the specific surface area of the hydrogel system, providing active sites for drug loading or cell adhesion. Therefore, the hydrogel system maintains a stable and continuous network structure, which is beneficial for gas exchange and nutrient transport between the wound and the external environment, thereby accelerating wound healing and improving the recovery effect of the hydrogel system.

[0087] (6) Adhesion experiment: A small piece of hydrogel was adhered to the index finger, and was adhered to a small piece of paper, a glass piece, the five internal organs of a mouse (heart, spleen, kidney, lung, liver), a bottle cap, and an iron nail, respectively, to evaluate the adhesion performance of the hydrogel. As shown in Figure 14 , the hydrogel system exhibits good adhesion performance and can firmly adhere to a variety of different surfaces. On a small piece of paper and a glass piece, the adhesion effect of the hydrogel system is very significant, and it can effectively adhere to the index finger and remain stable. In the experiment on the five internal organs of a mouse, the hydrogel system can well adapt to the shape and tissue structure of the organ surface, successfully avoiding the shedding of the hydrogel system, indicating that the hydrogel system has good biocompatibility. For metal surfaces such as bottle caps and iron nails, the hydrogel system can also firmly adhere, showing excellent performance of the hydrogel system on different surfaces. This strong adhesion of the hydrogel system may be attributed to the hydrogen bond interaction between chlorogenic acid and chitosan, which effectively enhances the adhesion between the hydrogel system and different adhesion materials. That is, the hydrogel system formed by the grafting of activated chlorogenic acid and chitosan with oxystylopine has good multi-faceted adaptability and stability, which provides strong support for the application of the hydrogel system in the field of wound dressings.

[0088] (7) Molding test: The hydrogel system was poured into a heart-shaped and square mold in advance, placed for one day, and the hydrogel system was removed from the mold the next day. The morphology of the hydrogel system was observed, and the results are shown in Figure 2 , which shows that the hydrogel system can be molded into different shapes through different molds, that is, the hydrogel system has good plasticity.

[0089] (8) Self-healing experiment: A clean and suitable culture dish was taken, and the prepared hydrogel system was slowly poured into the culture dish. A sharp knife was used to cut the hydrogel system into 4 parts, and the cutting process was as smooth as possible. Then the culture dish carrying the cut hydrogel system was placed in a constant temperature oven at room temperature, and the state change of the hydrogel at different time periods was observed every 1 h and recorded.

[0090] The results are shown inFigure 15 As shown, it can be observed that the hydrogel system cut into different pieces gradually heals. The gap of the four hydrogel systems gradually narrows in the first hour, while in the second hour, the different hydrogel systems begin to adhere to each other, in the third hour, the adhesion between the different hydrogel systems is more close, and in the fourth hour, the different hydrogel systems cut apart are completely bonded together. This shows that the hydrogel system has good self-healing performance.

[0091] In summary, the preparation method of the hydrogel system based on oxidized Gastrodia stem polysaccharide provided by the embodiments of the present application optimizes the structural stability and long-acting moisturizing adhesion of the hydrogel to reduce the replacement frequency of the hydrogel system, and at the same time, relies on the synergistic biological effects of multiple active ingredients to improve the recovery effect of the hydrogel system.

[0092] In addition, the preparation method of the hydrogel system based on oxidized Gastrodia stem polysaccharide provided by the embodiments of the present application first modifies the Gastrodia stem polysaccharide by oxidation to enhance the reaction activity of the Gastrodia stem polysaccharide and chitosan, and then covalently bonds chitosan and activated chlorogenic acid, so as to prepare a composite hydrogel system of oxidized Gastrodia stem polysaccharide-chitosan-chlorogenic acid. The hydrogel system can not only maintain the moist environment of the wound by using the moisturizing and antioxidant effects of oxidized Gastrodia stem polysaccharide, but also reduce the risk of bacterial infection of the wound and accelerate wound healing by virtue of the anti-inflammatory and antibacterial effects of chlorogenic acid.

[0093] In addition, the hydrogel system based on oxidized Gastrodia stem polysaccharide provided by the embodiments of the present application crosslinks the grafts between the oxidized Gastrodia stem polysaccharide sample and chlorogenic acid and chitosan by Schiff base reaction to form a crosslinking network, which endows the hydrogel system with self-healing ability and environmental response characteristics. In addition, the crosslinking network can endow the hydrogel system with a slow-release effect, gradually release the oxidized Gastrodia stem polysaccharide and chlorogenic acid components, prolong the drug effect of the hydrogel system, and avoid the degradation of the oxidized Gastrodia stem polysaccharide and chlorogenic acid directly exposed to air, sunlight or high temperature. The hydrogel system is expected to replace traditional adjuvants in future clinical applications, become a promising wound repair agent, and has a long use time, which can reduce the replacement frequency of the hydrogel system.

[0094] The above only describes specific embodiments of the present application, enabling those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features of the present application.

Claims

1. A method for preparing a hydrogel system based on oxidized Gastrodia elata stem polysaccharide, characterized in that, The preparation method includes: The stems of Gastrodia elata were subjected to water extraction and alcohol precipitation to obtain Gastrodia elata stem polysaccharide samples; The Gastrodia elata stem polysaccharide sample was oxidized using sodium periodate to introduce aldehyde groups into the Gastrodia elata stem polysaccharide sample, resulting in an oxidized Gastrodia elata stem polysaccharide sample. The chlorogenic acid was activated using an activating agent to obtain activated chlorogenic acid; Chitosan and the activated chlorogenic acid were grafted together to obtain a chitosan-grafted chlorogenic acid graft. The crosslinking promoter, the oxidized Gastrodia elata stem polysaccharide sample, and the chitosan-grafted chlorogenic acid were subjected to a Schiff base reaction to obtain a hydrogel system containing oxidized Gastrodia elata stem polysaccharide.

2. The preparation method according to claim 1, characterized in that, The mass m1 of sodium periodate and the mass m2 of the Gastrodia elata stem polysaccharide sample satisfy the following condition: m1:m2 = (2.5 to 3.5):

1.

3. The preparation method according to claim 1, characterized in that, The amount of the activator n1 and the amount of the chlorogenic acid n2 satisfy: n1:n2 = (10 to 12): (2.8 to 3.0).

4. The preparation method according to claim 1 or 3, characterized in that, The activator comprises N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, wherein the amount of N-hydroxysuccinimide n3 and the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride n4 satisfy the following: n3:n4 = (5 to 6):(5 to 6).

5. The preparation method according to claim 1, characterized in that, The mass m3 of the oxidized Gastrodia elata stem polysaccharide sample, the mass m4 of the crosslinking promoter, and the mass m5 of the graft satisfy the following: m3:m4:m5=12:1:(14 to 16).

6. The preparation method according to claim 1 or 5, characterized in that, The crosslinking accelerator includes zinc chloride.

7. The preparation method according to claim 1, characterized in that, The oxidation treatment time is ≥6 hours; and / or The grafting time is ≥24 hours.

8. A hydrogel system based on oxidized Gastrodia elata stem polysaccharide, characterized in that, The hydrogel system is prepared by the preparation method according to any one of claims 1 to 7.

9. The hydrogel system according to claim 8, characterized in that, The hydrogel system comprises oxidized Gastrodia elata stem polysaccharide, wherein the amount of aldehyde groups n5 in the oxidized Gastrodia elata stem polysaccharide and the mass m6 of the hydrogel system satisfy: n5:m6 ≥ 2.8 × 10⁻⁶. -3 :

1. If the unit of n1 is mol, then the unit of m6 is g.

10. A wound dressing, characterized in that, The wound dressing comprises the hydrogel system of claim 8 or 9.